Effect of Omega 3 and Vitamin B12 on the spermogram, histomorphometry of the reproductive organs and body temperatures with infrared thermography in Wistar rats - Yamada, L. M.M.; Souza, C. D.; Branco, I. T.; Andrade, I. B.; Deak, F. L.G.B.; Bastos, G. P.; Silva, J. G.; Amoris, J. V.R.; Yamada, L. Y.; Goiozo, P. F.I.; Cremasco, C. P. [UNESP]; Filho, L.R.A. Gabriel [UNESP]; et al. (FapUNIFESP (SciELO), 2019)
The objective of this study was to study the effect of Omega 3 and vitamin B12 on spermogram, histomorphometry of reproductive organs and body temperature with infrared thermography in Wistar rats. Sixteen rats were used in four groups (n= 4) who received daily injections for 30 days. Control Group - saline solution; Group Omega 3 - fish oil 1g/kg; Group B12 - vitamin B12 3μg and Group Omega 3 + B12 - fish oil 1g/kg and vitamin B12 3μg. Thermographic images of body were obtained. On the 30 th day the rats were sacrificed and analyzes of sperm morphology and histomorphometry were performed. Data were submitted to analysis of variance and Tukey's test at 5%. The surface temperature of the scrotum was higher in group B12 (P < 0.05). There were no differences between groups (P > 0.05) for eyeball temperatures. There was a correlation between scrotal temperature and distal cytoplasmic droplet (P= 0.678). Elevation of scrotum temperature results in an increase in the percentage of distal cytoplasmic droplets. The temperature of the eyeball is not significantly influenced by Omega 3 and vitamin B12. Omega 3 reduces the seminiferous epithelium and vitamin B12 minimizes this effect.

Objetivou-se estudar o efeito do ômega 3 e da vitamina B12 no espermograma, na histomorfometria dos órgãos reprodutivos e na temperaturas do corpo com termografia infravermelha em ratos Wistar. Utilizaram-se 16 ratos, em quatro grupos (n=4), que receberam injeções diárias por 30 dias, sendo: grupo controle - solução salina; grupo ômega 3 - óleo de peixe 1g/kg; grupo B12 - vitamina B12 3μg; e grupo ômega 3 + B12 - óleo de peixe 1g/kg e vitamina B12 3μg. Imagens termográficas de áreas do corpo foram obtidas. No 30° dia, os ratos foram sacrificados e realizaram-se as análises de morfologia espermática e histomorfometria. Os dados foram submetidos à análise de variância e ao teste de Tukey a 5%. A temperatura da superfície do escroto foi superior no grupo B12 (P < 0.05). Não houve diferenças entre grupos (P > 0.05) para temperaturas do globo ocular. Houve correlação entre temperatura da superfície do escroto e porcentagem de gota citoplasmática distal (P=0,678). A elevação da temperatura do escroto resulta no aumento da porcentagem de gotas citoplasmáticas distais. A temperatura do globo ocular não sofre influência significativa do ômega 3 e da vitamina B12. O ômega 3 reduz o epitélio seminífero, e a vitamina B12 minimiza esse efeito.
Efeito do ômega 3 e da vitamina B12 no espermograma, na histomorfometria dos órgãos reprodutivos e nas temperaturas do corpo com termografia infravermelha em ratos Wistar
Keywords: Aparelho reprodutor; Cianocobalamina; Cyanocobalamin; Fish oil; Reproductive system; Termograma; Thermogram; Óleo de peixe